The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/jcc.21124
|View full text |Cite
|
Sign up to set email alerts
|

Stability of carbon‐centered radicals: Effect of functional groups on the energetics of addition of molecular oxygen

Abstract: In this paper we examine a series of hydrocarbons with structural features which cause a weakening of the C-H bond. We use theoretical calculations to explore whether the carbon-centered radicals R(*) which are created after breaking the bond can be stabilized enough so that they resist the addition of molecular oxygen, i.e. where the reaction R(*) + O(2) --> ROO(*) becomes energetically unfavorable. Calculations using a B3LYP-based method provide accurate bond dissociation enthalpies (BDEs) for R-H and R-OO(*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(56 citation statements)
references
References 24 publications
1
52
0
Order By: Relevance
“…In contrast to the expectations based on the spin density analysis, C11 exhibits a significantly higher activation barrier than C9 and C13 considering the preferred planar substrate structure. This follows the general trend for product formation 25 , but falls in disagreement with the calculations of Hu and Pratt 26 . The latter found that the barrier for insertion of O 2 in a pentadienyl radical to the central carbon atom would be about 1 kcal/mol higher in energy than to an end position.…”
Section: Resultssupporting
confidence: 69%
“…In contrast to the expectations based on the spin density analysis, C11 exhibits a significantly higher activation barrier than C9 and C13 considering the preferred planar substrate structure. This follows the general trend for product formation 25 , but falls in disagreement with the calculations of Hu and Pratt 26 . The latter found that the barrier for insertion of O 2 in a pentadienyl radical to the central carbon atom would be about 1 kcal/mol higher in energy than to an end position.…”
Section: Resultssupporting
confidence: 69%
“…Five factors have been shown to be of importance in the literature: (1) stabilization by benzylic resonance; (2) spin delocalization onto oxygen or another unreactive heteroatom; (3) stereoelectronic effects; (4) electron‐withdrawing effects; and (5) steric effects. In the investigation by Wright et al, a set of model structures was chosen in order to examine these factors, and by calculating BDEs with a modified DFT method, they were able to confirm the importance of each of the above‐mentioned factors. From our own calculations, and using data from Wright's investigation, one particularly important observation can be made: to generate a sufficiently stabilized carbon‐centered radical, it is insufficient to provide stabilization from only a single functional group (e.g., heteroatom, aromatic ring, or a double bond).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, xanthene having the methylene (-CH 2 -) group also showed a high reactivity. The stereo-electronic effect causes the C-H bond in the methylene -CH 2 -group between two aromatic rings of phenolic dimers and xanthene weaken synergistically, which makes the structure of phenolic dimers (Ar-CH 2 -Ar) and xanthene instable and thus vulnerable to be attacked by a nucleophile for electrophilic substitution [28]. Besides, these structures (phenolic dimers with methylene groups and xanthene) have a high number of non-substituted o-/p-sites (i.e.…”
Section: Gc-ms Analysismentioning
confidence: 99%